A kind of silk fibroin-based electrospinning composite nanofiber membrane and preparation method thereof

By combining silk fibroin with modifiers such as carvacrol, composite nanofiber membranes were prepared by electrospinning, which solved the problems of insufficient antibacterial performance and large fiber brittleness of existing materials, and achieved efficient antibacterial, flexibility and biological Compatibility.

CN119113182BActive Publication Date: 2025-02-25HUAQIAO UNIVERSITY

Patent Information

Application Number
CN202411585424.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-25
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing silk fibroin-based biological nanofiber materials have insufficient antibacterial properties and are highly brittle in fibers, making it difficult to meet the practical application needs.

Method used

Compound nanofiber membranes are prepared by placing modified agents such as silk fibroin and carvacrol into spinning liquid, and electrospinning is used to prepare. The method includes obtaining silk fibroin, mixing it with a modifier, and electrospinning to form a nanofiber membrane.

Benefits of technology

The prepared silk fibroin-based electrospin composite nanofiber membrane has excellent antibacterial properties, improves the flexibility and mechanical properties of the fibers, and maintains good biocompatibility and water permeability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113182B_ABST
    Figure CN119113182B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a silk fibroin-based electrostatic spinning composite nanofiber membrane, comprising the following steps: S1, obtaining silk fibroin; S2, preparing a spinning solution with a silk fibroin and a modifier; the modifier is one or more of carvacrol, chitosan or chitosan quaternary ammonium salt; S3, preparing a nanofiber membrane by electrostatic spinning. The nanofiber membrane has a high antibacterial rate, high water permeability, good biocompatibility, excellent food preservation performance and excellent biodegradability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silk fibroin-based electrostatic spinning composite nanofiber membrane and a preparation method thereof, belonging to the technical field of biomedical materials such as bandages, dressings, absorbent pads or surgical supplies. Background Art

[0002] In the field of biomedical materials technology, such as tissue regeneration and wound healing, tissue engineering and controlled drug delivery, bandages, dressings, absorbent pads or surgical supplies are often used. With the development of modern scientific research, new green and environmentally friendly biodegradable materials are gaining more and more attention, but bacterial contamination of biodegradable materials is a common problem and a serious threat to human health worldwide. Therefore, the development of multifunctional biomedical materials with antibacterial properties and anti-infection capabilities is a continuous goal for biomedical applications.

[0003] Domesticated silkworms are the main source of commercial silk. The silk fibroin extracted from them has been approved by the US Food and Drug Administration as a new type of biomaterial. It has excellent biocompatibility, biodegradability, safety and non-toxicity, and has the advantages of wide sources, high yield, and easy processing into a variety of material forms. It has developed into one of the most widely used natural polymers in the field of biomedical materials. In recent years, nanotechnology has developed rapidly. Electrospinning technology has the advantages of relatively simple operation, wide application range and wide material sources, and has been widely used in the preparation of nanofibers. So far, many antibacterial silk fibroin-based bio-nanofiber materials have been developed by combining silk fibroin with synthetic and / or natural polymers through electrospinning technology. They have high surface area to volume ratio, porosity and adjustability, and can be used in the fields of tissue regeneration and wound healing, tissue engineering and controllable drug delivery.

[0004] Since silk fibroin itself has poor antibacterial activity and bacterial infection is the main reason for the failure of such materials, people have been trying to give silk fibroin-based bio-nanofibers antibacterial properties and expand their application range. In order to obtain fiber nanomaterials with good antibacterial properties, it is crucial to select suitable antibacterial agents. At present, the mainstream method for preparing antibacterial silk fibroin-based bio-nanofibers is to dip the electrospun silk fibroin fiber membrane into antibacterial agents or soak it in various antibacterial solutions. This method is limited in the amount of antibacterial substances loaded on the surface of the fiber material, and the stability and release rate of the antibacterial substances cannot be guaranteed.

[0005] In addition, silk fibroin fibers are very brittle and difficult to meet practical application requirements. Summary of the invention

[0006] The present invention provides a silk fibroin-based electrostatic spinning composite nanofiber membrane and a preparation method thereof, which can effectively solve the above problems.

[0007] The present invention is achieved in that:

[0008] A method for preparing a silk fibroin-based electrospinning composite nanofiber membrane comprises the following steps:

[0009] S1, obtain silk fibroin;

[0010] S2, preparing a spinning solution with silk fibroin and a modifier; the modifier is carvacrol; the ratio of silk fibroin to carvacrol is 2.5-3.5 g: 1 mL;

[0011] S3, preparing a nanofiber membrane by electrospinning; the process parameters of the electrospinning method are: solution flow rate of 4-6 μL / min, voltage of 10-20 kV, distance between needle and roller of 8-12 cm, and rotation speed of the roller of 280-320 r / min.

[0012] In some embodiments, in step S1, the method for obtaining silk fibroin is: subjecting silk to degumming, drying, silk dissolution, dialysis, centrifugation and freeze-drying in sequence to obtain silk fibroin.

[0013] In some embodiments, the degumming is to wash the chopped silk cocoons three times in a sodium bicarbonate solution under boiling conditions with stirring; and then wash the alkali-washed silk into pieces in distilled water at 55-65° C. for four times.

[0014] In some embodiments, the silk dissolving step is to add the degummed silk into a lithium bromide solution and dissolve it at 55-65° C. for 3.5-4.5 hours.

[0015] In some embodiments, the dialysis bag has a molecular weight cut-off of 3500D.

[0016] In some embodiments, in step S2, the modifier further comprises chitosan or chitosan quaternary ammonium salt.

[0017] In some embodiments, in step S2, the method of preparing the silk fibroin and the modifier into a spinning solution is to completely dissolve the silk fibroin and the modifier in formic acid.

[0018] In some embodiments, in step S3, the spinning time of the electrospinning method is 10-12 hours.

[0019] A silk fibroin-based electrostatically spun composite nanofiber membrane prepared by the above method.

[0020] The beneficial effects of the present invention are:

[0021] The silk fibroin-based electrospinning composite nanofiber membrane prepared by the method of the present invention has excellent antibacterial properties and outstanding food preservation properties.

[0022] The silk fibroin-based electrospun composite nanofiber membrane prepared by the method of the present invention has good flexibility, greatly improves the brittleness of the pure silk fibroin fiber membrane while slightly reducing the tensile strength, and has excellent mechanical properties.

[0023] The silk fibroin-based electrostatic spinning composite nanofiber membrane prepared by the method of the invention has excellent biocompatibility and excellent water permeability.

[0024] The silk fibroin-based electrostatic spinning composite nanofiber membrane prepared by the method of the invention has excellent biodegradability and is an environmentally friendly material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 This is the extraction flow chart of silk fibroin.

[0027] Figure 2 The figure shows the preparation process of silk fibroin-based electrospinning composite nanofiber membrane.

[0028] Figure 3 This is a scanning electron microscope image of the silk fibroin-based electrospun composite nanofiber membrane.

[0029] Figure 4 Mechanical properties of silk fibroin-based electrospun composite nanofiber materials: (a) stress-strain curve, (b) tensile strength analysis, (c) elongation at break analysis, and (d) tensile modulus analysis.

[0030] Figure 5 Antibacterial properties of silk fibroin-based electrospun composite nanofiber membranes: (a) Photo of Escherichia coli bacterial growth, (b) Photo of Staphylococcus aureus bacterial growth, (c) Statistical graph of antibacterial rate, (d) Photo of inhibition of strawberry spoilage, (e) Color difference graph of strawberry before and after spoilage, (f) Graph of hardness, sweetness and total acidity of strawberry before and after spoilage.

[0031] Figure 6 Biocompatibility of silk fibroin-based electrospun composite nanofiber membranes: (a) optical image of cell staining in the cell proliferation experiment on the fiber membrane, (b) changes in the number of cells in the cell proliferation experiment on the fiber membrane; (c) actual picture of the water permeability experiment, in which the two bottles are separated by the sample fiber membrane; (d) actual picture of biodegradation. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] An embodiment of the present invention relates to a method for preparing a silk fibroin-based electrospun composite nanofiber membrane. The silk fibroin-based electrospun composite nanofiber membrane has excellent biocompatibility and biodegradability and is suitable for a variety of biomedical applications, such as bandages, dressings, absorbent pads or surgical supplies.

[0034] The specific steps of the preparation method are as follows:

[0035] First, in step S1, silk fibroin is obtained. Silk fibroin is a natural high molecular weight protein with good biocompatibility and biodegradability, and is an ideal raw material for preparing biomedical materials.

[0036] Next, in step S2, the silk fibroin and the modifier are configured into a spinning solution; the modifier is carvacrol. Carvacrol is a compound derived from nature, which is well-known for its unique antibacterial properties. This modifier can not only significantly improve the antibacterial properties of the composite nanofiber membrane, but surprisingly, it can also enhance the elongation at break of the composite nanofiber membrane. This means that by adding carvacrol, we can not only make the nanofiber membrane more resistant to bacterial and microbial invasion, but also improve its mechanical properties, making it have better ductility and flexibility when subjected to stretching or stress. This dual effect makes carvacrol a very valuable modifier, providing broader prospects for the application of composite nanofiber membranes.

[0037] In some embodiments, the ratio of silk fibroin to carvacrol is 2.5-3.5 g: 1 mL. This ratio helps ensure that the two components can be fully integrated to form a uniform mixed system so that they can exhibit optimal performance during subsequent use. By precisely controlling this ratio, the effective interaction between silk fibroin and carvacrol can be promoted, thereby improving the overall effect and stability of the product.

[0038] Finally, in step S3, the spinning solution is prepared into a nanofiber membrane by electrospinning technology. Electrospinning is an efficient nanofiber preparation technology that forms fibers in an electric field by applying high voltage and forms a fiber membrane on a collector. This technology can prepare nanofiber membranes with high specific surface area and high porosity, which are suitable for a variety of biomedical applications.

[0039] In some specific embodiments, the process parameters of the electrostatic spinning method involved in step S3 are set as follows: first, the solution flow rate for electrostatic spinning is accurately controlled within the range of 4 to 6 microliters per minute to ensure the uniformity and stability of the fiber. Secondly, the voltage range applied to the solution is set between 10 and 20 kilovolts, and this voltage range helps to form a slender and continuous fiber structure. In addition, the distance between the spinneret and the receiving drum is set between 8 and 12 centimeters, and such a distance helps the fiber to fully stretch and be deposited on the drum under the action of the electric field to form the required nanofiber film. Finally, the rotation speed of the receiving drum is set between 280 and 320 revolutions per minute, and this speed range helps the fiber to be evenly distributed on the drum surface, thereby obtaining a uniform nanofiber film. Through these fine process parameter controls, nanofiber materials with specific structures and properties can be effectively prepared.

[0040] The preparation method of the present invention not only obtains a silk fibroin-based electrospun composite nanofiber membrane with excellent antibacterial properties, but also significantly improves its elongation at break. In addition, the use of a modifier does not negatively affect the biocompatibility, water permeability and degradability of the nanofiber membrane, thereby ensuring its potential for application in the biomedical field. The nanofiber membrane has broad application prospects in the fields of wound dressings, tissue engineering scaffolds, and drug sustained-release carriers.

[0041] In some embodiments, in step S1, the method for obtaining silk fibroin is: subjecting silk to degumming, drying, silk dissolution, dialysis, centrifugation and freeze-drying in sequence to obtain silk fibroin.

[0042] In some embodiments, the degumming process involves placing the shredded silk cocoons in a sodium bicarbonate solution and stirring them under boiling conditions for alkali washing, and this process needs to be repeated three times to ensure that the sericin is completely removed; then, the alkali-washed silk is shredded again and washed in distilled water controlled at a temperature between 55 and 65 degrees Celsius. This washing process needs to be performed four times to ensure that the residual alkali solution and other impurities are removed, thereby obtaining clean silk fibers.

[0043] In certain embodiments, the silk dissolving process involves placing the degummed silk fibers into a solution containing lithium bromide, and then dissolving them for about 3.5 to 4.5 hours at a temperature of 55 to 65 degrees Celsius. This process is intended to further decompose and dissolve the silk fibroin in the silk fibers through the action of the lithium bromide solution, thereby obtaining a uniform solution that can be used in subsequent processing steps, such as spinning or making other silk materials. Precise control of temperature and time is essential to ensure the efficiency of the dissolving process and the quality of the dissolved solution.

[0044] In some embodiments, the dialysis bag has a molecular weight cut-off of 3500D.

[0045] In some specific embodiments, step S2 not only includes the addition of silk fibroin, but also further introduces chitosan or chitosan quaternary ammonium salt. The preparation method of this composite material can further enhance the performance and application range of the material. In these embodiments, the mass ratio between silk fibroin and chitosan or chitosan quaternary ammonium salt is carefully adjusted to ensure optimal performance and effect.

[0046] In some specific embodiments, the mass ratio is usually set in the range of 15-25:1, and such a ratio can ensure good compatibility and synergistic effect between the two materials, thereby showing excellent comprehensive properties such as mechanical properties, biocompatibility and degradability in the final product. Through this precise ratio, composite biomaterials with broad application prospects can be prepared, such as having potential application value in the fields of tissue engineering, drug delivery systems and wound dressings.

[0047] In some embodiments, in step S2, the method of preparing the silk fibroin and the modifier into a spinning solution is to completely dissolve the silk fibroin and the modifier in formic acid.

[0048] In some embodiments, in step S3, the spinning time of the electrospinning method is 10-12 hours. By controlling this time range, the uniformity and quality of the fibers can be ensured, thereby obtaining an ideal nanofiber membrane.

[0049] A silk fibroin-based electrospun composite nanofiber membrane prepared by the above method has a simple and economical preparation process and a relatively low cost. This fiber membrane not only has a high antibacterial rate, but also has excellent water permeability, ensuring its high efficiency in water exchange. In addition, it also exhibits good biocompatibility, which means that it is very compatible with biological tissues and cells and does not cause adverse reactions. In terms of food preservation, this fiber membrane performs well and can effectively extend the shelf life of food and maintain the freshness and nutritional value of food. The multifunctional silk fibroin-based composite nanofiber membrane prepared in the present invention will be widely used in the field of biological dressings and food preservation due to its unique properties. The versatility of this fiber membrane makes it an ideal candidate material, not only suitable for medical fields such as wound dressings, tissue engineering, etc., but also suitable for the food packaging industry, providing a safer and more environmentally friendly preservation solution for food. With the deepening of research and the advancement of technology, the performance of this fiber membrane is expected to be further improved, and its scope of application will continue to expand, making greater contributions to human health and environmental protection.

[0050] Example 1 Preparation of silk fibroin-based electrospun composite nanofiber membrane

[0051] (1) Extraction of silk fibroin: Figure 1 As shown, 10 g of chopped silk cocoons were placed in 2 L of 0.05 M sodium bicarbonate solution under boiling conditions and stirred for 30 min, and this was repeated three times. The silk after alkali washing was chopped and washed four times in 60 ° C distilled water. After drying, the silk was immersed in 9.3 M lithium bromide solution and dissolved at 60 ° C for 4 h. After being taken out, it was poured into a dialysis bag (the molecular weight cutoff of the dialysis bag is 3500D) and dialyzed for 3 days. The dialyzed solution was centrifuged at 11000 r / min for 10 min, and the silk solution was freeze-dried and finally ground into silk fibroin powder.

[0052] (2) Preparation of spinning solution: Figure 2 As shown, 0.6 g of silk fibroin powder and 200 μL of carvacrol (CRV) were weighed into a reaction bottle, and then 8.85 mL of formic acid was poured into the bottle and stirred at room temperature for 4 h to completely dissolve all the substances. Different volumes of carvacrol were then added and stirred at room temperature for 8 h to mix the solution evenly.

[0053] (3) Electrospinning: Figure 2 As shown, two 10mL syringes were used to draw equal amounts of spinning solution, fixed on the syringe pump, and pushed at a speed of 5μL / min. Under the conditions of a voltage of 15kV, a distance between the needle and the roller set to 10cm, and a roller speed of 300r / min, spinning was carried out for 12h to obtain the silk fibroin composite carvacrol fiber membrane SF-CRV.

[0054] Example 2

[0055] The difference from Example 1 is that the modifier is chitosan (CS) 0.03 g and carvacrol (CRV) 200 μL, and the other operations are the same as Example 1 to obtain silk fibroin composite chitosan and carvacrol fiber membrane SF-CS-CRV.

[0056] Example 3

[0057] The difference from Example 1 is that the modifier is 0.03 g of chitosan quaternary ammonium salt (HACC) and 200 μL of carvacrol (CRV), and the other operations are the same as Example 1 to obtain silk fibroin composite chitosan quaternary ammonium salt and carvacrol fiber membrane SF-HACC-CRV.

[0058] Comparative Example 1

[0059] The difference from Example 1 is that no modifier is used, and other operations are the same as Example 1 to obtain a silk fibroin fiber membrane SF.

[0060] Comparative Example 2

[0061] The difference from Example 1 is that the modifier is chitosan (CS) 0.03 g, and the other operations are the same as Example 1 to obtain silk fibroin composite chitosan fiber membrane SF-CS.

[0062] Comparative Example 3

[0063] The difference from Example 1 is that the modifier is chitosan quaternary ammonium salt (HACC) 0.03 g, and the other operations are the same as Example 1 to obtain silk fibroin composite chitosan quaternary ammonium salt fiber membrane SF-HACC.

[0064] The scanning electron microscope images and fiber diameter data of the silk fibroin-based composite nanofiber membranes prepared in Examples 1-3 and Comparative Examples 1-3 are shown in FIG. Figure 3 As shown in Table 1. Figure 3 As can be seen from Table 1, the composite nanofibers have good morphological characteristics, smooth surface, and no condensed beads. The diameter distribution of pure silk fiber is large, with an average diameter of 210.3nm; from the spinning process, the addition of carvacrol improves the spinnability of the spinning solution, and the fiber diameter is increased relative to the pure silk fiber membrane, with an average diameter increased to 349.1nm, and the fiber is smoother and more uniform; the composite fiber membranes with carvacrol and chitosan or chitosan quaternary ammonium salt added under the action of two modifiers SF-CS-CRV and SF-HACC-CRV have average diameters of 350.4nm and 129.2nm, respectively, and the silk protein fibers of the composite modifiers are all nanometer-level. This shows that the composite silk protein-based nanofiber membranes prepared in Examples 1-3 have good spinnability.

[0065] Table 1 Fiber diameter distribution of silk fibroin-based composite nanofiber membrane

[0066]

[0067] The mechanical properties of the silk fibroin composite nanofiber membranes SF prepared in Examples 1-3 and Comparative Examples 1-3, such as tensile strength, elongation at break and tensile modulus, were tested as follows: the fiber membrane was cut into dumbbell-shaped strips, wherein the strips were 25 mm long and 10 mm wide, the stretching part was 10 mm long and 5 mm wide, and the thickness of the strips was measured at the same time. At 30°C, the stretching rate was 3 mm·min -1 The tensile strength of the electrospun fibers was determined, and each fiber membrane was tested three times to calculate the average value. According to the test results, the tensile strength, elongation at break and tensile modulus of the electrospun fibers can be calculated by formulas 1, 2 and 3.

[0068]

[0069] Among them, σ t is the tensile strength (MPa), p is the tensile force at the fracture site (N), b is the width of the specimen (mm), and d is the thickness of the specimen (mm).

[0070]

[0071] Among them, ε t is the elongation at break (%), L0 is the original length of the specimen (mm), and L is the breaking length (mm).

[0072]

[0073] Where E is the tensile modulus, F is the tensile force (N), L0 is the original length of the sample (mm), b is the width of the sample (mm), d is the thickness of the sample (mm), is the change in sample length (mm).

[0074] The results are as follows Figure 4 As shown in Table 2. Figure 4As shown in Table 2, the pure silk fibroin nanofiber membrane SF is brittle, and the elongation at break is only 16.93%, which will greatly limit the use of silk fibroin. In the composite nanofiber membrane SF-CRV with carvacrol added, the elongation at break can be greatly increased to 79.31%. The elongation at break of the composite modifier nanofiber membrane SF-CS-CRV and SF-HACC-CRV after adding carvacrol, chitosan or chitosan quaternary ammonium salt will also increase to 26.12% and 47.09%, respectively. This proves that the silk fibroin-based composite nanofiber membranes prepared in Examples 1-3 have good flexibility, greatly improve the brittleness of the pure silk fibroin fiber membrane while slightly reducing the tensile strength, and have excellent mechanical properties.

[0075] Table 2 Mechanical properties of silk fibroin-based nanofiber materials

[0076]

[0077] Antibacterial activity experiment: Escherichia coli and Staphylococcus aureus were used as experimental strains, and the antibacterial activity of silk fibroin-based composite nanofiber membrane was tested by plate counting method. First, the bacterial culture was taken out from the freeze-dried bacterial vial and placed in 2 mL of culture medium (liquid culture medium: yeast peptone 10 g·L -1 , yeast extract powder 5 g·L -1 , sodium chloride 10 g·L -1 The mixture was then incubated at 37 °C overnight. The inoculated revived bacterial solution was diluted to 4 × 10 7 cfu·mL -1 The analysis was performed even if the refractive index of the new mixture reached 0.02. 10 μL of bacterial solution was taken and added to 1 mL of culture medium, and then the mixture was activated at 37 °C for 24 h. Both sides of the fiber were exposed to ultraviolet light for 10 minutes to eliminate surface bacterial contamination. Then, 15 mg of silk fibroin-based composite nanofiber membrane was placed in the bacterial culture medium on an ultra-clean workbench and activated at 37 °C and 150 r·min -1 Incubate in a constant temperature oscillator for 24 hours. Dilute the bacterial solution 10 times with culture medium in a clean bench. 5 Use a triangular glass spreading rod to evenly spread the diluted bacterial culture solution on the culture medium (solid culture medium: agar 20 g·L -1 , yeast peptone 10 g·L -1 , yeast extract powder 5 g·L -1 , sodium chloride 10g·L -1 ), prepare three replicate groups for each sample, cover the lid, seal it with sealing glue, incubate it in a 37 ℃ incubator for 24 hours, observe the growth of bacteria, and count the number of colonies.

[0078] The antibacterial rates of the composite nanofiber membranes prepared in Examples 1-3 and Comparative Examples 1-3 against Escherichia coli and Staphylococcus aureus were analyzed. Figure 5 As shown in (a)-5(c). As can be seen from 5(a)-5(c), compared with pure silk fibroin nanofibers without antibacterial effect, the composite nanofiber membranes all showed good antibacterial properties, especially the composite modifier nanofiber membrane of carvacrol and chitosan or chitosan quaternary ammonium salt had an antibacterial rate of up to 100% against Escherichia coli and Staphylococcus aureus, and a good antibacterial effect can be achieved during use. This shows that the silk fibroin-based nanofiber membranes prepared in Examples 1-5 also have excellent antibacterial properties.

[0079] Fruit preservation experiment: The silk fibroin-based composite nanofiber membrane was covered on the strawberry to observe the degree of decay of the strawberry. The color difference (L, a, b value) of the strawberry before and after decay was measured using a DS-200 spectrophotometer, the hardness was measured using a GY-4 fruit hardness meter, the sweetness was measured using a sweetness meter, and the total acidity was measured using titration. The experimental results are as follows: Figure 5 (d)-5(f). Figure 5 (d)-5(f) It can be seen that after 7 days, the fiber membrane not covered with pure SF and the control group without fiber membrane (control) showed moldy appearance, and the color difference, hardness, sweetness and total acid content changed greatly. The appearance and internal flesh of the strawberry covered with chitosan / carvacrol and chitosan quaternary ammonium salt / carvacrol composite modifier nanofiber membrane were intact, without mold, and the color difference, hardness, sweetness and total acid content changed little, which was basically consistent with fresh strawberries, and the effect was much better than that of pure SF and single modifier fiber membrane. This shows that the silk fibroin-based nanofiber membranes prepared in Examples 1-3 also have a good fruit preservation effect.

[0080] Biocompatibility experiment: Mouse leukemia cells of mononuclear macrophages (RAW 264.7) were selected as model cells for cell incubation. Silk fibroin-based composite nanofiber membranes were added to the culture dishes containing RAW 264.7 cells at a concentration of 300 μg mL −1 and 600 μg mL −1 , and incubated for 24 hours. The results are shown in Figures 6(a)-6(b). Figure 6 (a)-6(b) As can be seen, since silk itself has good biocompatibility and can promote cell proliferation, the test results show that the addition of the modifier has no adverse effect on the biocompatibility. This shows that the silk fibroin-based nanofiber membranes prepared in Examples 1-3 have good biocompatibility.

[0081] Water permeability experiment: Prepare two 10mL bottles filled with distilled water, separated by a silk fibroin fiber membrane, one of which is dyed with 5wt% rhodamine B dye, connect the two bottles, and observe the permeability of the dye over time. The results are as follows: Figure 6 (c) is shown. Figure 6 (c) It can be seen that within 4 hours, the Rhodamine B dye can basically completely penetrate the fiber membrane, and the added modifier has no effect on the water permeability of the fiber membrane itself, so the silk fibroin-based nanofiber membrane can maintain high water permeability during actual use. This shows that the silk fibroin-based nanofiber membranes prepared in Examples 1-3 have good water permeability.

[0082] The silk fibroin composite fiber membrane was buried in the soil to test its biodegradability. The experimental results are as follows: Figure 6 (d). Figure 6 (d) It can be seen that all fiber membranes can be completely degraded within about 3 weeks and are environmentally friendly materials.

[0083] In summary, the silk fibroin composite fiber membrane of the present invention has many advantages: simple preparation process, low cost, high antibacterial rate, high water permeability, good biocompatibility, excellent food preservation performance, and excellent biodegradability. The multifunctional silk fibroin-based composite nanofiber membrane prepared in the present invention can be widely used in a variety of biomedical applications, such as bandages, dressings, absorbent pads or surgical supplies, etc.

[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a silk fibroin-based electrospinning composite nanofiber membrane, characterized in that: The following steps are involved: S1, obtain silk fibroin; S2, preparing a spinning solution with silk fibroin and carvacrol; the ratio of the silk fibroin to carvacrol is 2.5-3.5 g: 1 mL; S3, preparing a nanofiber membrane by electrospinning; the process parameters of the electrospinning method are: solution flow rate of 4-6 μL / min, voltage of 10-20 kV, distance between needle and roller of 8-12 cm, and rotation speed of the roller of 280-320 r / min.

2. The method for preparing the silk fibroin-based electrospinning composite nanofiber membrane according to claim 1, characterized in that: In step S1, the method for obtaining silk fibroin is: subjecting silk to degumming, drying, silk dissolution, dialysis, centrifugation and freeze-drying in sequence to obtain silk fibroin.

3. The method for preparing the silk fibroin-based electrospinning composite nanofiber membrane according to claim 2, characterized in that: The degumming process comprises the following steps: alkali-washing the chopped silk cocoons three times in a sodium bicarbonate solution under a boiling state; and then chopped silk after alkali-washing is washed four times in distilled water at 55-65°C.

4. The method for preparing the silk fibroin-based electrospinning composite nanofiber membrane according to claim 2, characterized in that: The silk dissolving step is to add the degummed silk into a lithium bromide solution and dissolve it at 55-65° C. for 3.5-4.5 hours.

5. The method for preparing the silk fibroin-based electrospinning composite nanofiber membrane according to claim 2, characterized in that: The molecular weight cut-off of the dialysis bag for dialysis is 3500D.

6. The method for preparing the silk fibroin-based electrospinning composite nanofiber membrane according to claim 1, characterized in that: In step S2, the method of preparing the silk fibroin and carvacrol into a spinning solution is to completely dissolve the silk fibroin and carvacrol in formic acid.

7. The method for preparing the silk fibroin-based electrospinning composite nanofiber membrane according to claim 1, characterized in that: In step S3, the spinning time of the electrospinning method is 10-12 hours.

8. A silk fibroin-based electrospun composite nanofiber membrane prepared by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of chitosan-loaded fibroin-based antibacterial hemostatic material

    CN116585521A

  • Spinning solution, nanofiber membrane as well as preparation method and application of nanofiber membrane

    CN118895574A

Cited By

  • Silk fibroin composite spray coating as well as preparation method and application thereof

    CN121975438A